Developing a model of teaching patterns recognition based on sorting predict-think discovery for children aged 5-6 years. (March 2020) - Ulni, Elvira Khori; Suparno
Abstract: This study aimed to: (1) determine the feasibility of concept of pattern learning model based on sorting predict-think discovery, (2) determine the effectiveness of concept of pattern learning model based on sorting predict-think discovery. This research implemented several steps developed by Borg & Gall. The research subjects consisted of teachers and 172 children in 9 kindergartens in Sleman, Yogyakarta. The data was collected by using expert validation sheets, teacher questionnaires, and observation results. The data was obtained from5 treatments and time series. The results revealed that: (1) the results of the development of pattern learning model based on sorting predict-think discovery were very feasible to use, (2) pattern learning model based on sorting predict-think discovery is effective in developing children's ability in recognizing pattern. The effectiveness of pattern learning model based on sorting predict-think discovery was revealed by the significant improvements, after conducting five treatments for children 5 to 6 years old. The average ability of children to recognize linear patterns was 3.36, while the average ability of children to recognize cyclic patterns was 3.17, and the average ability of children to recognize hopscotch patterns was 3.03. Hence, the ability to recognize hopscotch patterns showed a slight increase. This happened since most children still have difficulty in memorizing, especially in drawing and creating patterns. Hopscotch patterns were patterns that have never been introduced and taught by teachers to children. Furthermore, all of children's abilities to recognize patterns had improved.